Medizinische Betreuung von jungen Frauen mit Ullrich-Turner-Syndrom in Deutschland - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Braemswig, Juergen; Hauffa, Berthold P.; Holterhus, Paul-Martin; Mohnike, Klaus; Schmidt, Heinrich; Stalla, Guenter K.; Wabitsch, Martin; Woelfle, Joachim (Deutsche Medizinische Wochenschrift, 2020)
BACKGROUND: Many recommendations for medical care for women with Turner syndrome (TS) have been published in the past. There are no studies that analyse the care situation of the women in Germany until now. METHODS: The study was performed in 2015 based on a questionnaire that was completed by TS women (aged ≥ 18 years; median: 25 years). The questionnaire was devised by a French team and used with their permission. All women had received growth hormone treatment during childhood. The women were identified and addressed in writing through eleven cooperating centers and the support group. In all, 130 questionnaires were evaluated. RESULTS: 79 of the 130 women (61 %) stated that they had health problems. 38 % of the women were under medical care by only one physician and 42 % by two physicians. The gynecologist was mentioned most often (by 80.3 %), followed by the family physician (53.8 %). ENT was mentioned as a problem system by 35 %, but only 3 % of the women attended an ENT physician. The question as to whether at least one of the following examinations (measurements of blood pressure, blood sugar, blood fats, liver function and/or thyroid hormones, echocardiographic and/or audiogram examination) had been performed during a period of 4 years was answered as follows: blood pressure (85 %), blood sugar (47 %), blood fats (41 %), liver function (46 %), thyroid hormones (44 %), echocardiography (57 %) and audiogram (35 %). A comprehensive examination was performed in 9.8 % of the women. 103 women (80.5 %) received sexual hormone replacement therapy. 76 women were on further drugs; thyroid hormones (44 %) and antihypertensive drugs (11 %) were stated most often. CONCLUSIONS: This is the first study which analyses the current situation of medical care of TS women in Germany. Our data show that medical care of young adult TS women is not optimal. The study cannot clarify the reasons. Due to the numerous and different comorbidities, the medical care of TS women is complex and should therefore be provided multidisciplinarily by different specialists under the direction of one physician.
CRIS-Team Scopus Importer:2020-03-13